Investigation and Evaluation of Embedded Controller Nodes of the Robotic Arm for Industrial Automation - Ramalingam, Mritha; Puviarasi, R. (International Science Press, 2016)
Robotic arm is widely used for industrial automation. Most programming methods used today involve some degree of programming knowledge or involve creating an entire three dimensional workspace to virtually program the robotic arm. The two major key drawbacks preventing from a more widespread use of robotic arm is the cost involved and the difficulty in programming the arm as per the unique requirements of the job at hand. To address these two limitations, this research work aims at reducing the cost of the industrial arm by using multiple low cost embedded processors working in a coordinated and distributed fashion. Also, this work implements a master -slave based control system for real time control andprogramming of the robotic arm. This proposed master-slave control system is analogous to lead by nose programming method and overcomes the mentioned limitations.